Working With Refugees' Health During COVID-19—The Experience of Health- and Social Care Workers in Sweden - Mangrio, Elisabeth; Zdravkovic, Slobodan; Strange, Michael (Frontiers in Public Health, 2022)
In Sweden, often seen as one of the most egalitarian countries, the Covid-19 pandemic exposed high levels of health inequity, especially harming people with a refugee background. Despite its image as a refugee-friendly country, individuals who have entered Sweden as refugees have before the pandemic faced increasingly hostile conditions, including significant practical obstacles to maintaining their health and wellbeing. In that context, the aim of this paper is to better understand how Swedish health- and social workers have reacted to the health- and social needs of refugees during the pandemic. The Swedish case is particularly interesting because, as seen in the paper, health- and social workers were tasked with communicating health guidance to refugees who were sometimes more reliant on information from abroad where the consensus on Covid-19 restrictions ran contrary to the approach recommended by the Swedish public health authority. Method The chosen method for this study was qualitative and involved 13 in-depth interviews with health- and social workers. Results The interviews showed that during the pandemic, the healthcare settings have remained open but with new precautions at reception areas impacting how refugees access healthcare. The shift over to digital tools has particularly impacted refugees, worsening already existing barriers to healthcare faced by those with refugee status. In addition, refugees often found their own ways to protect their health that ran contrary to the recommendations of health professionals, whilst also experiencing that it was not possible for them to follow given recommendations due to their living conditions. Conclusion Refugees have faced worsening barriers during the pandemic. Refugees have in general taken precautions and followed recommendations but faced challenges with social distancing due to isolation and crowed living. Public health authorities have often failed to acknowledge that individuals use increasingly diverse sources of knowledge when trying to protect their health, and that not everyone has access to the knowledge needed to access healthcare and social systems. Efforts and improvements are needed in order to prevent ill-health for this specific group while facing similar challenges in the future.